Pequenas polêmicas cotidianas : conflito no Facebook e construção social no Brasil contemporâneo - Petrik, Manuel (2019)
The emergence of social media in Brazil has mobilized the interest for new forms of sociality in the contemporary world. One of the most evident dimensions that can be seen in these digital environments are the conflicts and the controversies. This study observes, in three distinct weeks between the years 2017 and 2018, these manifestations in readers' comments in the pages of three newspapers on Facebook: Folha de São Paulo, El País e O Estado de São Paulo. Following the Grounded Theory as a method, thematic categories had been created for the posts of the newspapers and a typology of comments was formulated. The most salient result is the great interest of the readers for political subjects, following moral and behavioral topics. At the same time, in terms of users’ manifestations, the refractory tone of the comments stands out. The combination of political/ moral themes with this form of expression by the public constitutes the final reflection, supported on the work of Alfred Schütz, Peter Berger, Thomas Luckmann, Jean Baudrillard and Michel Maffesoli.